The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/hel.12410
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Helicobacter pylori infection 2017

Abstract: Over the last decade, it has been widely reported that the success of Helicobacter pylori eradication treatment is falling. A steady decline was observed in the number of patients achieving eradication with standard first-line triple therapy of two antibiotics and a proton pump inhibitor [1][2][3]. It now appears that the first-line eradication therapies most commonly used in everyday clinical practice fall considerably short of the 80% intention-to-treat (ITT) eradication rates that are considered the minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 115 publications
(194 reference statements)
0
25
0
1
Order By: Relevance
“…1 In Spain, H. pylori approximately infects 50% of the population, 2 but the prevalence is even higher in the northwest of Spain (up to 70%). 4 Current consensus guidelines highlight the importance of knowing local H. pylori resistance patterns, 1,2,5 and the use of therapeutic regimens that can ensure at least a 90% success rate in a particular region is recommended. 4 Current consensus guidelines highlight the importance of knowing local H. pylori resistance patterns, 1,2,5 and the use of therapeutic regimens that can ensure at least a 90% success rate in a particular region is recommended.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In Spain, H. pylori approximately infects 50% of the population, 2 but the prevalence is even higher in the northwest of Spain (up to 70%). 4 Current consensus guidelines highlight the importance of knowing local H. pylori resistance patterns, 1,2,5 and the use of therapeutic regimens that can ensure at least a 90% success rate in a particular region is recommended. 4 Current consensus guidelines highlight the importance of knowing local H. pylori resistance patterns, 1,2,5 and the use of therapeutic regimens that can ensure at least a 90% success rate in a particular region is recommended.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…3 In recent years, H. pylori eradication rates with conventional triple therapies have fallen to unacceptable levels. 4 Current consensus guidelines highlight the importance of knowing local H. pylori resistance patterns, 1,2,5 and the use of therapeutic regimens that can ensure at least a 90% success rate in a particular region is recommended. 1 In this context, the use of empiric triple clarithromycin-containing regimens is discouraged by most recent guidelines if local resistance to clarithromycin is >15%.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…5,6 This is attributable to the special gastric milieu of H. pylori, which leads to more difficult and complicated treatment regimens to achieve its successful eradication in contrast to other bacterial infections. Several strategies [7][8][9] have been proposed to increase the eradication rate and decrease the antibiotic resistance, including extension of treatment duration, increasing doses, using four-drug nonbismuth-containing (sequential, hybrid, and concomitant) and bismuth-containing quadruple therapies or even five-drug quintuple therapy, 10 use of other antibiotics such as levofloxacin, 9 azithromycin, 11 rifabutin, 12,13 and furazolidone, 14 using a high-dose proton pump inhibitor 15 or a novel potassium-competitive acid blocker (vonoprazan), [16][17][18] dual therapy, 8 use of bismuth-enhanced triple therapy 19 or susceptibility-guided therapy, [20][21][22] and the supplementation of probiotics. 8,23,24 However, the current multiple-dose antibiotic therapies still steadily increase the rate of worldwide antibiotic resistance, which becomes a leading international medical problem.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori (H pylori) is a gram-negative organism that causes gastric inflammation, peptic ulcer, gastric cancer, and mucosa-associated lymphoid tissue (MALT) lymphoma. 1 It is one of the most prevalent infectious agents in the world, and approximately half of Asian populations are infected with this organism. 2 The Kyoto global consensus report on H pylori gastritis defined H pylori as an infectious disease and suggested that all with H pylori infection should receive eradication treatment.…”
Section: Introductionmentioning
confidence: 99%